Optimasi Parameter Proses 3D Printing FDM Terhadap Akurasi Dimensi Menggunakan Filament Eflex - Pristiansyah Pristiansyah; Hasdiansah Hasdiansah; Sugiyarto Sugiyarto (Politeknik Manufaktur Negeri Bangka Belitung, 2019)
Fused Deposition Modeling (FDM) is a 3D Printing technique used to print products using filaments as material. The printed product has ideal geometric characteristics if it has meticulous size and perfect shape. One type of material that can be processed using 3D Printing FDM is flexible material. Research in terms of dimensional accuracy has been carried out on PLA and ABS materials. While research using flexible materials is still rarely done. From these problems, we need a study to get the process parameter settings on a 3D Printer machine that is optimal in obtaining dimensional accuracy using flexible materials. The research was carried out using the Prusa model DIY (Do It Yourself) 3D machine with FDM technology. The material used is Eflex type flexible filament with a diameter of 1.75 mm. The process parameters used in this study are flowrate, layer thickness, temperature nozzle, speed printing, overlap, and fan speed. Cuboid test specimens measuring 20 mm × 20 mm × 20 mm. Process parameter optimization using the Taguchi L27 Orthogonal Array method for dimensional accuracy testing. Optimal process parameter values for obtaining X dimension accuracy are 110% flowrate, 0.10 mm layer thickness, 210 °C nozzle temperature, 40 mm/s print speed, 75% overlap, and 50% fan speed. Y dimension is 120% flowrate, layer thickness 0.20 mm, nozzle temperature 230 °C, print speed 30 mm/s, overlap 75%, and fan speed 100%. As well as the Z dimension is 120% flowrate, layer thickness 0.30 mm, nozzle temperature 210 °C, print speed 30 mm/s, overlap 50%, and fan speed 100%.